Energy Absorption at High Strain Rate of Magnesium Alloy AZ31B - Mubasyir, M. M.; Abdullah, M. F.; Ku Ahmad, K. Z.; Othman, R. N. R.; Isahak, A. H. (International Journal of Integrated Engineering, 2020)
This paper presents the efficient energy absorption of magnesium alloy AZ31B with reinforcement carbon nanotubes (CNT) and lead (Pb). The high specific energy absorption demonstrated by CNT compared to metals is one of the criteria to improve the AZ31B performance against ballistic penetration. More ductility by adding Pb in the alloy also plays a vital role to increase the energy absorption capability. Four-cylinder shape AZ31B-based specimens are tested dynamically by using compression Split Hopkinson Pressure Bar (SHPB). The diameter and thickness of the specimen is 18 mm and 12.5 mm respectively. The striking velocity used in this work is 20 m/s. By equation of 1D wave propagation, stress-strain curve is plotted and the area under the curve is equivalent to energy absorption. The highest energy absorption is about 270 kJ with the increment of 47% compared to original AZ31B. This increment is consistent with the higher strain rate experienced by the specimen during the test. The strain rate determined from the study is 1300 per second compared to original AZ31B of 850 per second. The finding of this paper is the presence of CNT and lead could improve the energy absorption performance as the strain rate of the specimen also increased.